FROM MADHAB TO SOCIAL DOGMA: THE TABLIGHIJEMAAT’S FLUIDITY OF TEACHINGS AND THE INTEGRATION OF UMMAH - Ilyasin, Mukhammad (LENTERA, 2017)
Tablighi Jamaat is one of the largest Muslim organization in the world. Despite lacking formal form of organization like other Islamic organization in general, the members of the Tablighi Jamaat is well known for their loyalty and discipline in implementing the principles of the organization, especially regarding the organizations’ guidelines on conducting da’wa to Muslims with different religious background such as madhab affiliation. This paper, therefore, aims at explaining the strategy of performing da’wa applied by the Tablighi Jamaat in plural social settings. Findings suggest that the Tablighi Jamaat utilized the notion of equality as its most important principle of da’wa. The idea of equality is actualized through several mechanism like madhab fluidation, desacralization of madhab and demadhabization. In this context, every member of the Tablighi Jamaat has the same opportunity to be da’I (preacher) as well as to be mad’u (audience).Keywords: Tablighi Jamaat, Strategy of Da’wa, Desacralization, Demadhabization and Madhab Fluidation.